2016
DOI: 10.1139/cjpp-2015-0457
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV protects cardiomyocytes from anoxia/reoxygenation injury by upregulating the expression of Hes1 protein

Abstract: Astragaloside IV (ASI), a traditional Chinese medicine, is a main active ingredient of Astragalus membranaceus. Many clinical studies have found that ASI protects cardiomyocytes in cardiovascular diseases, but the underlying mechanisms remain obscure. The aim of this study was to investigate the molecular mechanisms responsible for the protective effects of ASI in cardiomyocytes from anoxia/reoxygenation (A/R) injury. According to the previous studies, we hypothesized that the cardioprotective effects of ASI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Mitochondrial membrane potential is essential for an integrated appraisal of mitochondrial function (30). The loss of mitochondrial membrane potential is mediated by the MPTP opening, resulting in the release of cytochrome c from mitochondria (15). Our present data showed that mitochondrial fission inhibition suppressed aldosterone-induced MPTP opening and mitochondrial membrane potential loss.…”
Section: Discussionsupporting
confidence: 54%
“…Mitochondrial membrane potential is essential for an integrated appraisal of mitochondrial function (30). The loss of mitochondrial membrane potential is mediated by the MPTP opening, resulting in the release of cytochrome c from mitochondria (15). Our present data showed that mitochondrial fission inhibition suppressed aldosterone-induced MPTP opening and mitochondrial membrane potential loss.…”
Section: Discussionsupporting
confidence: 54%
“…H9c2 cells were incubated at 37°C in a 5% CO 2 incubator (Forma™ 310, Thermo Fisher, USA) with high glucose (4.5 g/l glucose) DMEM (Solarbio, Beijing, China) by adding 13% FBS (foetal bovine serum, WISENT, Canada) and antibiotics (100 U/ml penicillin and 100 μg/ml streptomycin, Solarbio, Beijing, China). The hypoxia/reoxygenation (H/R) cell model was set up to imitate an ischaemia/reperfusion (I/R) model in vitro [14][15][16][17]. Briefly, after different pretreatments, H9c2 cells were cultured in hypoxic solution (sodium lactate 40 mM, NaH 2 PO 4 0.9 mM, NaHCO 3 6 mM, MgSO 4 1.2 mM, HEPES 20 mM, CaCl 2 1.8 mM, NaCl 98.5 mM, KCl 10 mM, pH 6.8) and incubated at 37°C with 5% CO 2 and 0.1% O 2 in a hypoxic chamber (Proox model C21, BioSpherix Ltd., USA) for 3 h. H9c2 cells were subsequently cultured in reoxygenation solution (glucose 5.5 mM, NaH 2 PO 4 0.9 mM, NaHCO 3 20 mM, MgSO 4 1.2 mM, HEPES 20 mM, CaCl 2 1.8 mM, NaCl 129.5 mM, KCl 5 mM, pH 7.4) and incubated at 37°C and 95% O 2 /5% CO 2 in a reoxygenation chamber for 2 h. All experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…1) In recent years, in vitro and in vivo studies have shown that AS-IV is protective against myocardial ischemiareperfusion injury (IRI) 2,3) and its mechanism of action is mainly related to anti-oxidative stress and anti-inflammatory pathways. [4][5][6] However, the specific target molecules and signaling pathways involved still await further study. Heme oxygenase (HO-1) is recognized as an important anti-oxidative stress and tissue protective enzyme that produces CO and biliverdin, and can also induce multiple anti-oxidative and anti-inflammatory signaling pathways, which significantly reduce cellular damage and protect organ function.…”
Section: Introductionmentioning
confidence: 99%